All-solid-state lithium ion battery and application thereof

By designing the lithium alloy negative electrode and the modified sulfide electrolyte in an all-solid-state lithium-ion battery, an interface layer is formed to avoid direct contact between lithium metal and the sulfide electrolyte, the water sensitivity of the sulfide electrolyte and the dendrite problems of the lithium alloy negative electrode are solved, and the battery performance and safety are improved.

CN119695248APending Publication Date: 2025-03-25ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411930031.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Sulfide electrolytes are sensitive to water, pose safety risks, and are easily decomposed by chemical reduction of lithium metal, resulting in poor battery polarization and cycling performance. At the same time, the lithium alloy negative electrode is prone to generate dendrites pierce the solid electrolyte under high current density, causing a battery to be short-circuited.

Method used

The design of all-solid-state lithium-ion battery is adopted, including lithium alloy negative electrode, solid electrolyte diaphragm and positive electrode sheet. The chemical formula of the alloy layer is LixZy, where 0.5≤x/y≤9, and Z is selected from the elements such as Ge, In, Sn, Sb, Bi, etc. The chemical formula of the sulfide electrolyte is LiaP1-bMbScOdXe, M includes Al, Ga, In, Ti, etc., X is selected from Cl, Br or I. Through the design of the alloy layer and the sulfide electrolyte, an interface layer is formed to avoid direct contact between the lithium metal and the sulfide electrolyte, and the lithium deposition process is optimized.

Benefits of technology

It improves the conductivity stability and air stability of the sulfide electrolyte, avoids negative electrode volume expansion and battery short circuit, improves Coulomb efficiency and the stability of lithium deposition and peeling, extends the cycle life of the battery and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210301910000161
    Figure BDA0005210301910000161
Patent Text Reader

Abstract

The invention provides an all-solid-state lithium ion battery and application thereof. The all-solid-state lithium ion battery comprises a positive pole piece and a negative pole piece, the lithium alloy negative electrode comprises a negative electrode current collector and an alloy layer arranged on one side of the negative electrode current collector, the chemical formula of the alloy layer is LixZy, x / y is larger than or equal to 0.5 and smaller than or equal to 9, and Z is selected from one or more of Ge, In, Sn, Sb, Bi, Si, Al, Mg, Zn or Ag; the solid electrolyte membrane is arranged between the positive pole piece and the lithium alloy negative pole, the alloy layer is arranged close to the solid electrolyte membrane, and the solid electrolyte membrane comprises sulfide electrolyte Li P < 1-b > M Sc < d > X < e >, a < lt >; 6, 0lt; blt; 1, 1.5 1t; clt; ct; 5, 0lt; dlt; 2.5, 4lt; c + dlt; 5, 1lt; lt, lt; 2; m comprises one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X comprises one or more of Cl, Br or I. According to the all-solid-state lithium ion battery and the application thereof provided by the invention, the air stability of sulfide electrolyte can be improved, and the performance and the safety of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an all-solid-state lithium ion battery and applications thereof. Background Art

[0002] All-solid-state lithium-ion batteries use solid electrolytes instead of traditional organic liquid electrolytes and separators, which can simplify battery design, improve battery safety, and increase energy density, and are expected to become one of the important power sources in the future. In all-solid-state lithium-ion batteries, solid electrolytes are one of the most critical components.

[0003] Sulfide electrolytes have room temperature ionic conductivity comparable to that of liquid electrolytes, and are soft and have good wettability at the interface with metallic lithium, which has attracted much attention. However, sulfide electrolytes are extremely sensitive to water and release toxic gases instantly when exposed to a water-containing environment, posing a safety hazard. Sulfide electrolytes are easily chemically reduced by nucleophilic lithium metals, leading to continuous decomposition of sulfide electrolytes, rapid increase in interfacial impedance, increased polarization of the battery, and poor cycle performance. At the same time, the lithium alloy negative electrode is prone to generate dendrites that pierce the solid electrolyte at high current density, causing a short circuit in the battery and causing battery safety issues. Summary of the invention

[0004] The present invention proposes an all-solid-state lithium-ion battery and its application. The all-solid-state lithium-ion battery and its application provided by the present invention can improve the stability of the conductivity of the sulfide electrolyte and enhance the air stability. It can avoid the pressure-induced deformation of the soft metal lithium sheet negative electrode causing the negative electrode volume expansion, and can avoid the direct contact between the sulfide electrolyte and the lithium metal, improve the coulomb efficiency and the stability of lithium deposition and stripping, and maintain stable lithium deposition and stripping behavior even at a high discharge depth, thereby improving the performance and safety of the battery.

[0005] To solve the above technical problems, the present invention is implemented through the following technical solutions.

[0006] The present invention provides an all-solid-state lithium-ion battery, comprising at least:

[0007] Positive electrode;

[0008] A lithium alloy negative electrode, the lithium alloy negative electrode comprising a negative electrode current collector and an alloy layer arranged on one side of the negative electrode current collector, the chemical formula of the alloy layer is Li x Z y , wherein 0.5≤x / y≤9, and Z is selected from one or more of Ge, In, Sn, Sb, Bi, Si, Al, Mg, Zn or Ag; and

[0009] A solid electrolyte film is disposed between the positive electrode plate and the lithium alloy negative electrode. The alloy layer is disposed adjacent to the solid electrolyte film. The solid electrolyte film includes a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M includes one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, and X includes one or more of Cl, Br, or I.

[0010] In an embodiment of the present invention, M includes at least one of Sb, In, or Bi, and X is selected from Cl.

[0011] In an embodiment of the present invention, Z includes at least one of Sb, In, or Bi.

[0012] In an embodiment of the present invention, based on the total molar amount of the alloy layer, the sum of the molar contents of Sb, In, or Bi is 10% to 66.7%.

[0013] In an embodiment of the present invention, the negative electrode current collector includes one of nickel, titanium, gold, chromium, molybdenum, copper, stainless steel, or a carbon current collector, and the thickness of the negative electrode current collector is less than 7 μm.

[0014] In an embodiment of the present invention, the thickness of the alloy layer is 5 μm to 45 μm.

[0015] In an embodiment of the present invention, the lithium alloy negative electrode is obtained by the following method:

[0016] Weigh Li and Z according to stoichiometry in a stainless steel container and heat to obtain a Li x Z y alloy melt;

[0017] Apply the Li x Z y alloy melt uniformly on the surface of the negative electrode current collector and cool to room temperature to obtain the alloy negative electrode.

[0018] In an embodiment of the present invention, the particle size of the sulfide electrolyte is 1 μm to 10 μm, and the ionic conductivity is greater than 3 mS / cm; the thickness of the solid electrolyte film is 30 μm to 100 μm.

[0019] In one embodiment of the present invention, the solid electrolyte membrane includes a sulfide electrolyte and a binder, and the content of the sulfide electrolyte in the solid electrolyte membrane is 80wt% to 99wt%; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binder, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber.

[0020] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.

[0021] In summary, the present invention proposes an all-solid-state lithium-ion battery and its application, which can improve the stability of the conductivity of the sulfide electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. It can avoid the pressure-induced deformation of the soft metal lithium sheet negative electrode causing the negative electrode volume expansion. The doped modified sulfide electrolyte forms an interface layer at the interface with the lithium alloy negative electrode, which can promote Li + The fast transfer kinetics of the lithium ion battery can homogenize the electric field and balance the local current density, thereby regulating the nucleation and growth of lithium. The interfacial layer can avoid direct contact between the sulfide electrolyte and lithium metal, and the alloy sites formed in the negative electrode interface and bulk phase can optimize the lithium deposition process, improve the coulombic efficiency and the stability of lithium deposition and stripping, and maintain stable lithium deposition and stripping behavior even at high discharge depths, thereby improving the performance and safety of the battery. DETAILED DESCRIPTION

[0022] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0023] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0024] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The present invention provides an all-solid-state lithium-ion battery, which includes a positive electrode sheet, a lithium alloy negative electrode, and a solid electrolyte membrane. In the present invention, the all-solid-state lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery, or a cylindrical battery. The present invention does not specifically limit the type and type of the all-solid-state lithium-ion battery.

[0026] In one embodiment of the present invention, the lithium alloy negative electrode includes a negative electrode current collector and an alloy layer arranged on one side of the negative electrode current collector, wherein the negative electrode current collector includes, for example, one of the current collectors that do not undergo alloying reaction with metallic lithium, such as nickel, titanium, gold, chromium, molybdenum, copper, stainless steel or carbon current collector, and the thickness of the negative electrode current collector is less than 7μm.

[0027] In one embodiment of the present invention, the chemical formula of the alloy layer is Li x Z y , where 0.5≤x / y≤9, and Z includes, for example, one or more of Ge, In, Sn, Sb, Bi, Si, Al, Mg, Zn, or Ag. When the metal lithium content in the alloy layer is low, the active lithium loss is high during the cycle, and the battery is prone to battery failure in the later stage of the cycle. When the metal lithium content in the alloy is high, a metal lithium phase is prone to appear in the alloy negative electrode body phase, and lithium dendrites are prone to appear in local areas, resulting in a short circuit in the battery.

[0028] In one embodiment of the present invention, Z includes at least one of Sb, In or Bi, and the sum of the molar contents of Sb, In or Bi is 10% to 66.7% based on the total molar amount of the alloy layer. Compared with the metal lithium sheet, the lithium alloy negative electrode obtained in the present application has a certain mechanical strength, is not prone to mechanical deformation, and avoids pressure-induced deformation of the soft metal lithium sheet negative electrode causing negative electrode volume expansion. And the alloy layer can optimize the lithium deposition process, improve the coulomb efficiency and the stability of lithium deposition stripping, and maintain stable lithium deposition stripping behavior even at high discharge depth and high rate current, thereby improving the performance and safety of the battery.

[0029] In one embodiment of the present invention, when the alloy layer is a Li-In alloy, the Li-In alloy includes one of Li3In3, Li3In2, Li3In, Li2In or Li5In4 alloys, etc. When the alloy layer is a Li-Bi alloy, the Li-Bi alloy includes one of Li3Bi or Li3Bi2 alloys, etc. When the alloy layer is a Li-Sb alloy, the Li-Sb alloy includes one of Li2Sb or Li3Sb alloys, etc.

[0030] In one embodiment of the present invention, the alloy layer is obtained, for example, by the following steps, which specifically include:

[0031] According to the stoichiometric weight, single lithium and single Z were weighed in a stainless steel container and heated to obtain Lix Z y Alloy melt;

[0032] Lithium (Li) x Z y The alloy melt is uniformly coated on the surface of the negative current collector and cooled to room temperature to obtain the alloy negative electrode.

[0033] In one embodiment of the present invention, elemental lithium and elemental Z are heated, for example, in an inert atmosphere, such as helium or argon. The heating and melting temperature is, for example, 200°C to 300°C, the heating reaction time is, for example, 20 min to 30 min, and the thickness of the formed alloy layer is, for example, 5 μm to 45 μm. The thickness of the alloy layer is controlled to match the thickness of the positive electrode plate and reduce the energy density loss.

[0034] In one embodiment of the present invention, a solid electrolyte membrane is disposed between the positive electrode plate and the lithium alloy negative electrode. The alloy layer is disposed close to the solid electrolyte membrane. The solid electrolyte membrane includes a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2, M includes one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, etc., and X is selected from one or more of Cl, Br, or I, etc. Introducing M elements and O elements into the sulfide electrolyte rich in halogen elements will form P-O and M-S bonds in the crystal structure, thereby improving the intrinsic resistance to atmospheric degradation and effectively reducing the generation of H2S, enhancing the air stability and chemical stability of the sulfide electrolyte. In addition, when using this sulfide electrolyte to assemble an all-solid-state lithium-ion battery, the doped and modified sulfide electrolyte forms LiCl with a higher interfacial energy and Li2O with a higher ionic conductivity at the interface with the lithium alloy negative electrode. At the same time, the sulfide electrolyte reacts with the alloy layer to form alloys such as Li-Sb / Li-Bi / Li-In alloys. The interfacial layer includes Li2O, LiCl, and Li-Sb / Li-Bi / Li-In alloys, etc. Li2O has a high intrinsic ionic conductivity, and the Li-Sb / Li-Bi / Li-In alloy can promote Li +The fast transfer kinetics of the electric field can be uniformized, balancing the local current density, thereby regulating the nucleation and growth of Li. The interface layer can avoid direct contact between the sulfide electrolyte and the lithium metal, and the alloy sites formed in the negative electrode interface and bulk phase can optimize the lithium deposition process, improve the coulombic efficiency and the stability of lithium deposition and stripping, and maintain stable lithium deposition and stripping behavior even at high discharge depths, thereby improving the cycle life of all-solid-state lithium-ion batteries.

[0035] In one embodiment of the present invention, M includes at least one of Sb, In or Bi, for example. Since the ionic radius of Sb, In or Bi is moderate, and the ionic radius of these elements is close to the ionic radius of the main elements in the sulfide electrolyte, such as sulfur and phosphorus, they can more easily replace the position of the main elements when doped without causing excessive lattice distortion. In addition, Sb, In or Bi has moderate electronegativity, and can form a stable chemical bond with the sulfur element in the sulfide, which is difficult to be damaged by external influences, so that the sulfide electrolyte has high stability and specific reactivity, and can improve the stability of the conductivity of the sulfide electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material.

[0036] In one embodiment of the present invention, X is selected from halogen elements, and depending on the halogen, the degree of anion disorder between the 4a and 4c sites in the sulfide electrolyte crystal structure is different, ranging from a small amount of anti-site defects when X is I to 60% site disorder when X is Cl, and the lithium conductivity of these compounds mainly depends on the degree of disorder occupied by anion and cation sites. Therefore, X is selected from Cl, for example, to improve the ionic conductivity and electrochemical stability of the sulfide electrolyte and improve the voltage stability. The value range of b is 0<b≤0.1. In a specific embodiment of the present invention, when M is +5 valence, b is optimally 0.04, and when M is +3 valence, b is optimally 0.02, so as to improve the cycle performance of the lithium ion battery.

[0037] In one embodiment of the present invention, the sulfide electrolyte is obtained by the following preparation method: according to the chemical formula of the sulfide electrolyte, a Li source, a P source, an M source, an S source and an X source are mixed in stoichiometric amounts, and then placed in a ball mill for ball milling to obtain a sulfide electrolyte precursor powder; the sulfide electrolyte precursor powder is calcined at a preset temperature to obtain a sulfide electrolyte.

[0038] In one embodiment of the present invention, according to the chemical formula of the sulfide electrolyte Li a P 1-b M b S c O d X e, the Li source, P source, M source, S source and X source are uniformly mixed according to stoichiometric ratio, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5, the M source is selected from one or more of oxides of M or sulfides of M, the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, As2S5, As2S3, Sb2S5, Sb2S3, Bi2S5, Bi2S3, Al2S3, Ga2S3, In2S3 or Sc2S3, the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, and the O element in the chemical formula comes from the oxide of M. After the raw materials are mixed evenly, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1500 rpm, and the ball milling time is, for example, 1 h to 48 h, to obtain a sulfide electrolyte precursor powder.

[0039] In one embodiment of the present invention, the sulfide electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 400°C to 600°C, and the calcination time is 1h to 18h, to obtain a sulfide electrolyte. In one embodiment of the present invention, the particle size of the sulfide electrolyte is, for example, 1μm to 10μm, and the ion conductivity is greater than 3mS / cm.

[0040] In one embodiment of the present invention, after obtaining the sulfide electrolyte, a solid electrolyte membrane is obtained, for example, by dry preparation or wet preparation. In one embodiment of the present invention, for example, a solid electrolyte membrane is obtained by dry preparation. Specifically, the sulfide electrolyte and the binder are blended according to the mass ratio to obtain a mixed powder; the mixed powder is repeatedly rolled at a preset temperature for a preset time to obtain a solid electrolyte membrane. Among them, the content of the sulfide electrolyte in the solid electrolyte membrane is, for example, 80wt% to 99wt%, and the binder is, for example, selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber. The preset temperature is 60°C to 100°C, and the preset rolling time is 30min to 120min.

[0041] In another embodiment of the present invention, for example, a solid electrolyte membrane is prepared by a wet method. Specifically, a sulfide electrolyte and a binder are added to a low-polarity organic solvent according to a mass ratio, and a vacuum degasser is used for vacuum treatment to obtain a uniform mixed slurry. The mixed slurry is coated on the surface of the substrate by a sprayer or a coating machine, and after removing the solvent, a solid electrolyte membrane coating is obtained. The solid electrolyte membrane coating is peeled off from the substrate to obtain a sulfur solid electrolyte membrane. Among them, the content of the sulfide electrolyte in the solid electrolyte membrane is, for example, 80wt% to 99wt%, and the binder is, for example, selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binders, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber. The low-polarity solvent is, for example, selected from one or more combinations of toluene, xylene, n-pentane, hexane or cyclohexane, and is, for example, xylene. The substrate is, for example, selected from one of aluminum foil, copper foil, polyester board (PET), release paper, polytetrafluoroethylene board (PTFE) or glass board. In one embodiment of the present invention, the solid electrolyte membrane coating prepared by a wet process is transferred to the positive electrode plate by, for example, transfer printing.

[0042] In another embodiment of the present invention, the thickness of the obtained solid electrolyte membrane is, for example, 30 μm to 100 μm.

[0043] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric, and the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.

[0044] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent, and a binder, wherein the positive electrode active material is selected from, for example, a positive electrode active material with a layered structure, such as one or more combinations of lithium cobalt oxide (LCO), nickel cobalt manganese lithium oxide (NCM), or nickel cobalt aluminum lithium oxide (NCA). The positive electrode active material is selected from, for example, an olivine structured positive electrode active material, such as one or more combinations of lithium iron phosphate (LFP) or lithium iron manganese phosphate (LFMP). The positive electrode active material is selected from, for example, a spinel structured positive electrode active material, such as one or more combinations of lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), or lithium-rich manganese-based (LMR).

[0045] In one embodiment of the present invention, the positive electrode active material is, for example, LiNbO3 coated LiNi 0.9 Co 0.05 Mn 0.05O2, wherein the coating layer has a thickness of, for example, 5 nm to 15 nm. In this embodiment, the positive electrode active material is obtained, for example, by a wet coating method. By coating with LiNbO3, the discharge capacity and cycle stability of the all-solid-state lithium-ion battery can be improved, the mechanical properties of the material can be enhanced, and the service life of the battery can be extended.

[0046] In one embodiment of the present invention, the positive electrode electrolyte is, for example, the above-mentioned sulfide electrolyte. The conductive agent is, for example, selected from one or more combinations of conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF), Ketjen black, acetylene black, graphene, carbon nanotubes, porous carbon, etc., and the binder is, for example, selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene butadiene rubber (SBR), etc.

[0047] In one embodiment of the present invention, the positive electrode active material is, for example, LiNbO3 coated LiNi 0.9 Co 0.05 Mn 0.05 O2, the positive electrode electrolyte is, for example, the above-mentioned sulfide electrolyte, the conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the binder is, for example, HNBR. The positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are dispersed in a low-polarity solvent such as xylene according to a mass ratio of 70:25:2:3, and the amount of xylene added is adjusted to control the solid content of the slurry to, for example, about 55%. The slurry is coated on an aluminum foil by a doctor blade method, and the coated aluminum foil is air-dried at 90°C to 110°C for 2h to 3h, and then rolled and compacted at 60°C at a pressure of 95MPa to obtain a positive electrode sheet, and the thickness of the positive active layer is, for example, 80μm to 120μm. The present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder, and can be selected according to actual needs.

[0048] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and lithium alloy negative electrode are placed in sequence, so that the solid electrolyte membrane is between the positive electrode sheet and the lithium alloy negative electrode to play an isolating role, and the sheets are stacked to form a bare cell. The bare cell is placed in a shell and sealed, and the shell is, for example, an aluminum-plastic bag, etc., and then the process of standing, forming and dividing the capacity is carried out to obtain a finished soft-pack solid-state lithium-ion battery. Among them, the assembly process of the all-solid-state lithium-ion battery is completed in a glove box with an inert atmosphere.

[0049] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0050] Example 1

[0051] Preparation of lithium alloy negative electrode: In an argon atmosphere glove box, metallic lithium and metallic indium were mixed in a stainless steel tank at a molar ratio of 3:2 (x / y=1.5), heated at 220°C to obtain a molten alloy solution, reacted for 20 minutes, then the alloy solution was scraped onto a copper foil and naturally cooled to room temperature to obtain a lithium alloy negative electrode. The thickness of the alloy layer was 30 μm, and the chemical formula of the lithium-indium alloy was Li3In2.

[0052] Preparation of solid electrolyte membrane: Li 5.54 P 0.98 In 0.02 S 4.4 O 0.1 Cl 1.5 and PTFE binder at a mass ratio of 99:1 for 5 minutes, then roll-pressed at 80°C, gradually narrowing the roll gap to 40 μm, and repeatedly rolling at this roll gap for 60 minutes to obtain a solid electrolyte membrane with a thickness of 40 μm.

[0053] Preparation of positive electrode sheet: LiNi coated with LiNbO3 positive electrode active material 0.9 Co 0.05 Mn 0.05O2, the coating thickness is 10nm. The positive electrode electrolyte is, for example, the above-mentioned sulfide electrolyte, the conductive agent includes Super P and VGCF, and the mass ratio of Super P and VGCF is 1:1, and the binder is HNBR. In an environment with a dew point of -30°C, the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are dispersed in xylene, for example, according to a mass ratio of 70:25:2:3, and the amount of xylene added is adjusted to control the solid content of the slurry to 55%. The slurry is coated on an aluminum foil by a doctor blade method, and the coated aluminum foil is dried at 100°C for 2h, and then rolled and compacted at 60°C at a pressure of 95MPa to obtain a positive electrode sheet, wherein the thickness of the positive electrode active layer is, for example, 100μm.

[0054] All-solid-state lithium-ion battery assembly: stack the prepared positive electrode sheet, solid electrolyte membrane and lithium alloy negative electrode in sequence, so that the solid electrolyte membrane is between the positive electrode sheet and the lithium alloy negative electrode to play an isolating role, and stack the sheets to the bare battery cell. Put the bare battery cell into an aluminum-plastic bag, and then stand it, form it and divide it into different volumes to obtain a finished soft-pack solid-state lithium-ion battery.

[0055] Example 2

[0056] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 1.

[0057] Example 3

[0058] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 P 0.96 Sb 0.04 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0059] Example 4

[0060] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Al 0.02 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0061] Example 5

[0062] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Ti 0.02 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0063] Example 6

[0064] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 1.

[0065] Example 7

[0066] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.62 P 0.94 Bi 0.06 S 4.1 O 0.09 Cl 1.5 , other operations remain the same as those in Example 1.

[0067] Example 8

[0068] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 1.

[0069] Example 9

[0070] In the alloy layer, metal indium is replaced by metal bismuth, the molar ratio of metal lithium to metal bismuth is 3:1 (x / y=3), and other operations are consistent with Example 2.

[0071] Example 10

[0072] In the alloy layer, metal indium is replaced by metal antimony, the molar ratio of metal lithium to metal antimony is 3:1 (x / y=3), and other operations are consistent with Example 2.

[0073] Embodiment 11

[0074] In the alloy layer, metal indium is replaced by metal germanium, the molar ratio of metal lithium to metal germanium is 3:1 (x / y=3), and other operations are consistent with those in Example 2.

[0075] Example 12

[0076] In the alloy layer, metal indium is replaced by metal tin, the molar ratio of metal lithium to metal tin is 3:1 (x / y=3), and other operations are consistent with those in Example 2.

[0077] Embodiment 13

[0078] In the alloy layer, the molar ratio of metallic lithium to metallic indium is 1:2 (x / y=0.5), and other operations are consistent with those in Example 2.

[0079] Embodiment 14

[0080] In the alloy layer, the molar ratio of metallic lithium to metallic indium is 9:1 (x / y=9), and other operations are consistent with those in Example 2.

[0081] Embodiment 15

[0082] The thickness of the alloy layer is 5 μm, and other operations are consistent with those in Example 2.

[0083] Example 16

[0084] The thickness of the alloy layer is 45 μm, and other operations are consistent with those in Example 2.

[0085] Comparative Example 1

[0086] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 PS 4.5 Cl 1.5 , the alloy layer is replaced by a single lithium layer, and other operations are consistent with Example 1.

[0087] Comparative Example 2

[0088] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 In 0.02 S5Cl 1.5 , other operations remain the same as those in Example 1.

[0089] Comparative Example 3

[0090] The sulfide electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 PS 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0091] Comparative Example 4

[0092] The alloy layer is replaced by a single lithium layer, and other operations are consistent with Example 2.

[0093] Comparative Example 5

[0094] In the alloy layer, the molar ratio of metallic lithium to metallic indium is 1:4 (x / y=0.25), and other operations are consistent with those in Example 2.

[0095] Comparative Example 6

[0096] In the alloy layer, the molar ratio of metallic lithium to metallic indium is 50:1 (x / y=50), and other operations are consistent with those in Example 2.

[0097] Comparative Example 7

[0098] The thickness of the alloy layer is 2 μm, and other operations are consistent with those in Example 2.

[0099] In Examples 1-16 and Comparative Examples 1-7 of the present invention, different sulfide electrolytes and lithium alloy negative electrodes are used to prepare all-solid-state lithium-ion batteries. Some characteristics of the sulfide electrolyte and the lithium alloy negative electrode are shown in Table 1. The conductivity of the sulfide electrolyte is obtained, for example, by an AC impedance method. The all-solid-state lithium-ion batteries obtained in Examples 1-16 and Comparative Examples 1-7 are tested, and the test results are shown in Table 1.

[0100] In one embodiment of the present invention, the 0.5C / 0.5C room temperature cycle capacity retention rate test of the all-solid-state ion battery is to charge and discharge the prepared all-solid-state lithium ion battery at a low rate of 0.1C / 0.1C for 2 weeks at 25°C, and the test voltage range is 2.5V~4.2V, and then charge and discharge at a rate of 0.5C / 0.5C, and record the first cycle discharge capacity at 0.5C rate. When the discharge capacity reaches 80% (80% SOH) of the first cycle discharge capacity at 0.5C rate, the test stops and the number of cycles at room temperature is recorded. The calculation formula of the capacity retention rate is as follows: Capacity retention rate (%) = (discharge capacity / discharge capacity of the first cycle) × 100%.

[0101] Table 1. Battery performance test results in Examples 1-16 and Comparative Examples 1-7

[0102]

[0103] As shown in Table 1, by comparing Example 1 with Comparative Examples 2 and 3, Example 8 with Comparative Example 2, and Example 2 with Comparative Example 4, it can be seen that by performing dual doping modification on the P and O positions of the sulfide electrolyte, the stability of the sulfide electrolyte to air and metallic lithium can be improved. Further matching the sulfide electrolyte with a lithium alloy negative electrode can improve the reversibility of negative electrode lithium deposition and stripping, avoid the risk of lithium dendrites still forming during high-rate charge and discharge to cause battery short circuit, and improve the cycle life of the all-solid-state lithium-ion battery.

[0104] Please refer to Table 1. By comparing Examples 1-8 and Comparative Examples 2-3, it can be seen that single or double doping at the P and O positions will cause a decrease in the ionic conductivity of the sulfide electrolyte, and the ionic conductivity decreases rapidly with the increase of the doping element. This is because when the element is doped into the 4b position, the carrier concentration increases, and the ionic conductivity increases slightly. However, as the doping elements increase, more vacancies are gradually occupied by lithium ions, ion conduction is hindered, and the conductivity decreases rapidly. P-position doping with different types of metal elements has a greater effect on the ionic conductivity of the electrolyte. Among them, the ionic conductivity of indium, bismuth or antimony elements is better than that of aluminum or titanium elements, and the corresponding all-solid-state lithium-ion battery has better cycle performance. Therefore, by regulating the type and content of the doping elements, the performance of the all-solid-state lithium-ion battery can be further optimized.

[0105] As shown in Table 1, by comparing Examples 2 and 8 with Comparative Examples 1 and 4, it can be seen that when the doped sulfide electrolyte is used in combination with the lithium alloy negative electrode, such as Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 When single-element lithium and lithium-indium alloy are matched at the same time, the 80% SOH cycle number of all-solid-state lithium-ion batteries is increased from 425 weeks to 905 weeks. This is because the metal elements in the doped sulfide electrolyte can form a Li-M alloy-rich interface at the interface with the lithium metal negative electrode, balance the local current density, and regulate the lithium deposition behavior; at the same time, the presence of a large amount of alloy phase in the negative electrode body can optimize the lithium deposition process, improve the coulomb efficiency and the stability of lithium deposition stripping, and maintain stable and reversible lithium deposition stripping behavior even at high discharge depths, thereby improving the cycle life of all-solid-state lithium-ion batteries.

[0106] Please refer to Table 1. By comparing Examples 2 and 9-12, it can be seen that when different Z elements are selected for the alloy layer and the doping amount is the same, the cycle performance of the battery is at a higher level, but slightly different. Among them, when the Z element is indium, bismuth or antimony, the battery cycle performance is better than that of germanium and tin.

[0107] Please refer to Table 1. By comparing Example 2, Examples 13-14 and Comparative Examples 5-6, it can be seen that as the alloy layer Li x Z y When the value of x / y changes from large to small, the number of cycles of the all-solid-state lithium-ion battery increases and then decreases. This is because: when the content of metallic lithium in the alloy layer is low, more active lithium is lost during the cycle, and the battery is prone to diving in the later stage of the cycle; when the content of metallic lithium in the alloy is high, metallic lithium phase is prone to appear in the alloy negative electrode body phase, and lithium dendrites are prone to appear in local areas, causing battery short circuit. Therefore, the percentage content of metallic lithium in the alloy is regulated to improve the performance of the battery.

[0108] Please refer to Table 1. By comparing Example 2, Examples 15-16 and Comparative Example 7, it can be seen that as the thickness of the alloy layer increases, the cycle performance of the lithium-ion battery improves, but the subsequent improvement trend tends to be flat. Therefore, considering the cost and energy density, the thickness of the alloy layer is controlled to be 5μm to 45μm.

[0109] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state lithium-ion batteries, and the all-solid-state lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state lithium-ion battery, and therefore includes the advantages of the above-mentioned all-solid-state lithium-ion battery, which will not be elaborated here.

[0110] In summary, the present invention proposes an all-solid-state lithium-ion battery and its application, which can improve the stability of the conductivity of the sulfide electrolyte, enhance air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. It can avoid the pressure-induced deformation of the soft metal lithium sheet negative electrode causing the negative electrode volume expansion. The doped modified sulfide electrolyte forms an interface layer at the interface with the lithium alloy negative electrode, which can promote Li + The fast transfer kinetics of the lithium ion battery can homogenize the electric field and balance the local current density, thereby regulating the nucleation and growth of lithium. The interfacial layer can avoid direct contact between the sulfide electrolyte and lithium metal, and the alloy sites formed in the negative electrode interface and bulk phase can optimize the lithium deposition process, improve the coulombic efficiency and the stability of lithium deposition and stripping, and maintain stable lithium deposition and stripping behavior even at high discharge depths, thereby improving the performance and safety of the battery.

[0111] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0112] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. An all-solid-state lithium-ion battery, characterized in that: include: Positive electrode; A lithium alloy negative electrode, the lithium alloy negative electrode comprising a negative electrode current collector and an alloy layer arranged on one side of the negative electrode current collector, the chemical formula of the alloy layer is Li x Z y , wherein 0.5≤x / y≤9, and Z is selected from one or more of Ge, In, Sn, Sb, Bi, Si, Al, Mg, Zn or Ag; and A solid electrolyte membrane is disposed between the positive electrode sheet and the lithium alloy negative electrode. The alloy layer is disposed close to the solid electrolyte membrane. The solid electrolyte membrane comprises a sulfide electrolyte, and the chemical formula of the sulfide electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M comprises one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X comprises one or more of Cl, Br or I.

2. The all-solid-state lithium-ion battery according to claim 1, characterized in that: M includes at least one of Sb, In or Bi, and X is selected from Cl.

3. The all-solid-state lithium-ion battery according to claim 1, characterized in that: Z includes at least one of Sb, In, or Bi.

4. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The sum of the molar contents of Sb, In or Bi is 10% to 66.7% based on the total molar amount of the alloy layer.

5. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The negative electrode current collector includes one of nickel, titanium, gold, chromium, molybdenum, copper, stainless steel or a carbon current collector, and the thickness of the negative electrode current collector is less than 7 μm.

6. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The thickness of the alloy layer is 5 μm to 45 μm.

7. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The lithium alloy negative electrode is obtained by the following method: Li and Z were weighed in a stainless steel container according to the stoichiometric amount and heated to obtain Li x Z y Alloy melt; Li x Z y The alloy melt is evenly coated on the surface of the negative electrode current collector and cooled to room temperature to obtain the alloy negative electrode.

8. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The particle size of the sulfide electrolyte is 1 μm to 10 μm, and the ion conductivity is greater than 3 mS / cm; the thickness of the solid electrolyte membrane is 30 μm to 100 μm.

9. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The solid electrolyte membrane comprises a sulfide electrolyte and a binder, wherein the content of the sulfide electrolyte in the solid electrolyte membrane is 80wt% to 99wt%; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binder, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber.

10. An electronic device, characterized in that: An all-solid-state lithium-ion battery comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • Solid-state battery and preparation method thereof, and electric vehicle

    CN111370751A

  • Negative pole piece, solid-state battery and preparation method of negative pole piece

    CN113991058A

  • Lithium-silicon alloy negative electrode preparation method and sulfide all-solid-state battery

    CN114744161A

  • 3D double-layer lithium negative electrode, preparation method thereof and sulfide all-solid-state lithium ion battery containing 3D double-layer lithium negative electrode

    CN114843526A

  • Preparation method and application of Li-Al negative electrode material applied to solid-state battery

    CN116072859A